Impact of ethylene degreening treatment on sensory properties and consumer response to citrus fruits. (January 2020) - Morales, J.; Tárrega, A.; Salvador, A.; Navarro, P.; Besada, C.
Graphical abstract: Highlights: Degreening strongly affected consumers' expectations of maturity and quality. Degreening increased consumers' purchase intentions. The effect of degreening on physico-chemical properties depended on cultivar. Degreening did not affect the internal sensory properties that consumers perceived. Abstract: Degreening treatment is normally applied to early-season citrus varieties grown in the Mediterranean area in order to enhance the external colour when fruits have already reached internal maturity. Despite profound knowledge about the effect of ethylene on the physico-chemical quality of citrus fruit, less is known about its effect on consumers' expectations in the supermarket or consumer quality perceptions when they eat such fruit. In this study, three mandarin cultivars ('Owari', 'Clemenules' and 'Oronules') with two initial colours at harvest, and one orange cultivar, 'Navelina', were submitted to the degreening treatment under commercial conditions. The effect of treatment on both external and internal qualities perceived by consumers was evaluated. The main physico-chemical parameters were also determined. The degreening treatment slightly affected firmness, total soluble solids or acidity level in 'Owari' and 'Navelina'. However, sensory triangle tests, in which 100–122 consumers compared the internal quality of degreened fruit and control fruit, did not show significant differences between treatments for any of the studied cultivars. A survey based on images of citrus fruit was responded by 340 consumers; it showed that the degreening treatment strongly affected consumers' maturity expectations, which resulted in improved fruit liking expectations and increased the number of consumers willing to buy. The extent of this effect depended on the initial colour of the fruit submitted to degreening. In order to improve liking expectations, fruit should arrive on the market with an external colour index (CI = 1000a/Lb) between +10 and +20. We conclude that the ethylene degreening treatment, which did not have any effect on the internal quality that consumers perceive, is a potent postharvest tool to increase citrus fruit sales at the beginning of the season.